2018
DOI: 10.1093/pcp/pcy139
|View full text |Cite
|
Sign up to set email alerts
|

FPX is a Novel Chemical Inducer that Promotes Callus Formation and Shoot Regeneration in Plants

Abstract: Auxin and cytokinin control callus formation from developed plant organs as well as shoot regeneration from callus. Dedifferentiation and regeneration of plant cells by auxin and cytokinin stimulation are considered to be caused by the reprogramming of callus cells, but this hypothesis is still argued to this day. Although an elucidation of the regulatory mechanisms of callus formation and shoot regeneration has helped advance plant biotechnology research, many plant species are intractable to transformation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The validation of the new chemical inducer will not only benefit the process of transgenic performance but also add new knowledge to the functional analysis of developmental research in the model grass. FPX, as a new chemical inducer, has been employed in callus and shoot formation in mature and immature embryos in Brachypodium [21]. Our results also reinforced the ability of callus and shoot regeneration of FPX in Brachypodium .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The validation of the new chemical inducer will not only benefit the process of transgenic performance but also add new knowledge to the functional analysis of developmental research in the model grass. FPX, as a new chemical inducer, has been employed in callus and shoot formation in mature and immature embryos in Brachypodium [21]. Our results also reinforced the ability of callus and shoot regeneration of FPX in Brachypodium .…”
Section: Discussionsupporting
confidence: 81%
“…Recently, Nakano et al [21] demonstrated that FPX could function as a chemical inducer that promotes callus formation and shoot regeneration in plants. To examine if FPX can improve callus induction in our system, we conducted a comparative analysis between FPX and the regularly used chemical 2,4-D. Our results revealed that callus were indeed induced on the FPX medium.…”
Section: Resultsmentioning
confidence: 99%
“…A transcriptome is often already altered before organisms start to the physiological response to the treatment. Thus, transcriptome analyses of plants treated with small molecules provided insight into action mechanism of the molecules[17-19]. Thus, we conducted a genome-wide gene expression analysis to understand plant responses to nanocarbon molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Whole organs (cotyledons, hypocotyl, and root) was exposed to the treatment. It was demonstrated that 1-50 ÎŒM of bioactive small molecules change gene expression in Arabidopsis seedlings[17,18,20]. Thus we assumed that nanocarbon molecules may affect gene expression if these molecules have any biological activities.…”
Section: Resultsmentioning
confidence: 99%
“…Roots, shoots and whole plantlets can be subsequently regenerated from the callus and, for this reason, a precise control of callus formation and regeneration is critical for tissue culture and transformation technologies. Through a chemical screen, Nakano et al (2018) identified fipexide (FPX) as a potent inducer of dedifferentiation and callus formation. A transcriptomic analysis of FPX-induced/repressed genes revealed shared and unique effects of FPX and auxin/cytokinin treatments.…”
Section: Chemical Inducer Of Dedifferentiation and Callus Formationmentioning
confidence: 99%